Evaluasi Program Kartu Identitas Anak (KIA) di Kota Metro (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kota Metro) - Ike Fitti Wardani; Dedy Hermawan; Ita Prihantika (Jurnal Administrativa, 2023)
Implementation of the MCH program in Metro City has been going well, as evidenced by the achievement data on MCH ownership in 2022, only 1,411 children do not have MCH from the total number of children in Metro City aged 0-17 years less a day of 52,648 or means there are 51,237 children who already have MCH. This data also shows that the implementation of the MCH program in Metro City by the Disdukcapil of Metro City has passed the target set in the center, which is 45,629. However, related to the use of MCH in Metro City, it cannot be used optimally, such as MCH has not been made one of the mandatory requirements in school registration, MCH has also not been fully used in tourist attractions designated as one of the locations for MCH utilization or other benefits.